2020
DOI: 10.1021/acs.jafc.0c00007
|View full text |Cite
|
Sign up to set email alerts
|

Bromophenols from Symphyocladia latiuscula Target Human Monoamine Oxidase and Dopaminergic Receptors for the Management of Neurodegenerative Diseases

Abstract: Progressive degeneration of dopaminergic neurons in the substantia nigra is the characteristic feature of Parkinson’s disease (PD) and the severity accelerates with aging. Therefore, improving dopamine level or dopamine receptor signaling is a standard approach for PD treatment. Herein, our results demonstrate that bromophenols 2,3,6-tribromo-4,5-dihydroxybenzyl alcohol (1), 2,3,6-tribromo-4,5-dihydroxybenzyl methyl ether (2), and bis-(2,3,6-tribromo-4,5-dihydroxybenzyl) ether (3) from red alga Symphyocladia l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Interestingly, fucoxanthin was also identified as a dopamine agonist, where a molecular docking study suggested that it formed H-bonding with Ser196 and Asp115 of the D4 receptor, and Ser196 and Thr115 residues of D3 receptors [ 250 ]. The same group also identified some bromophenols derivatives as D3R and hD4R antagonists and studied the interaction and binding pattern by molecular docking [ 251 ].…”
Section: Algal Metabolites-based Drug Discovery and Designmentioning
confidence: 99%
“…Interestingly, fucoxanthin was also identified as a dopamine agonist, where a molecular docking study suggested that it formed H-bonding with Ser196 and Asp115 of the D4 receptor, and Ser196 and Thr115 residues of D3 receptors [ 250 ]. The same group also identified some bromophenols derivatives as D3R and hD4R antagonists and studied the interaction and binding pattern by molecular docking [ 251 ].…”
Section: Algal Metabolites-based Drug Discovery and Designmentioning
confidence: 99%
“…Moreover, BPs 6.1–6.3 exhibited more than 50% inhibition of self-induced A β 25–35 aggregation [ 9 ], which may be another mechanism for their anti-AD activity. In addition to anti-AD activity, BPs 6.1–6.3 have also been reported as inhibitors of human monoamine oxidase-A (hMAO-A) [ 109 ], which catalyzes the inactivation of multiple neurotransmitters in the treatment of PD. Furthermore, the same research group found that BPs 6.1–6.3 were also good dopamine D 3 /D 4 receptor agonists.…”
Section: Bioactivities Of Bps and Potential Use In Medicinementioning
confidence: 99%
“…Furthermore, the same research group found that BPs 6.1–6.3 were also good dopamine D 3 /D 4 receptor agonists. BP 6.3 was the most promising dopamine D 4 receptor agonist exhibiting EC 50 value at very low micromolar levels ( Table 5 ) [ 109 ]. Since AChE, BChE, BACE1, hMAO-A, and dopaminergic receptors are closely related to the neurodegenerative diseases such as AD and PD, these BPs compounds can possibly be developed as new drugs for the treatment of neurodegenerative disorders.…”
Section: Bioactivities Of Bps and Potential Use In Medicinementioning
confidence: 99%
See 2 more Smart Citations